Uso de recursos naturais por comunidades ribeirinhas amazônicas: bases para as políticas de concessões florestais - MELO JÚNIOR, Luiz Cláudio Moreira (2015)
This article deals with the relations between agrarian communities, natural resources, local knowledge and practices around the areas destined to forest concession processes along Mamuru and Arapiuns rivers, state of Pará. For primary data collection, questionnaires were filled with the population of these localities. Maps of natural resource use were constructed for each community studied, from the multiple uses of resources by communities. As a main conclusion the study indicates that a major challenge is that the policies of forest concession consider the areas of the communities as spaces for reproduction of the community social systems as well as collective use of natural resources. Otherwise, may suffer a strong anthropogenic pressure due to the attractive possibilities of use of natural resources for commercial and industrial purposes.